Review of bamboo-feeding leafhopper genus Bambusananus Li & Xing (Hemiptera: Cicadellidae: Deltocephalinae) with description of a new species from China - Yang, Lin; Chen, Xiang-Sheng (Zootaxa, 2012)
The bamboo-feeding leafhopper genus Bambusananus Li & Xing, 2011 is known to include five species in the world: B. bino-tatus (Li & Dai), B. bipunctatus (Li), B. furcatus Li & Xing, B. lii sp. nov. and B. maculipennis (Li & Wang). One new species,B. lii sp. nov. (Guizhou Province, China), is described and illustrated. Information on host plants and distribution for each species of Bambusananus is given along with a key to all known species.